Development of a low cost commercial switching mode power supply - Chung, Kok Pin. (2010)
This report present the design of a low cost high frequency (40KHZ) switch mode power supply (SMPS) with single output 75watt (Output Voltage=50Vdc and supply ampere from 0.5-1.5A) intended for commercial applications. The Input voltage fluctuation effect and the consequent input PF variation will be investigated and improved upon. At the very beginning, I initialize a preliminary power supply design with a known topology Fly-back. The functional and concept of SMPS was being studied to obtain the desired theory calculation from the components data sheet for each main block diagram. Subsequently the entire power supply circuits were modeled into a component-based system and perform circuit simulation with PSIM software. However due to unavailability of some components in the PSIM software, another set of alternate parts and circuit such as the non linear transformer and PI controller were selected from PSIM to replace the non-linear air gap transformer and opto-coupler feedback circuit. Lastly, the series of calculated values was used to compare the results obtained in software simulation. This approach spends more time than the earlier stage of theory design to isolate the problem and analyze the design flaw. However, with this software simulation, it reduce the development time and cost by providing more convincing design before developing the circuit into actual hardware. The experiment results are presented in the report to show the robustness and the effectiveness of the SMPS designed.